The Relationship Between Gadget Use And Socio-Emotional Development Of Preschool Children In Islamic Kindergarten Integrated Raudhatul Jannah Senapelan Alwashliyah Pekanbaru City - Qomariah, Siti; Selvi Panggabean; Dewi Sartika Siagian (Universitas Prima Indonesia, 2025)
Introduction According to WHO in 2020, there were at least 3.9 billion preschool-aged children using gadgets in the world. According to WHO in 2017, it was reported that 5-25% of preschool children experienced social emotional development disorders. The purpose of this study was to determine the relationship between gadget use and social emotional development in preschool children. This research method was correlational analytic with a cross-sectional approach, conducted at the Raudhatul Jannah Alwashliyah Senapelan Integrated Islamic Kindergarten, Pekanbaru City on May 27-June 3, 2025 with a population of 74 students. The sampling technique was purposive sampling, with a sample of 62 respondents. The instruments used were a gadget use duration questionnaire and KMME (Mental Emotional Problems Questionnaire). Data analysis used univariate frequency distribution analysis and bivariate Spearman rho statistical test (0.05). The results of the study stated that the Spearman rho statistical test produced ap value of 0.000 (p < 0.05), which means. So, it can be concluded that there is a relationship between the duration of gadget use and the social and emotional development of preschool children.